National Integration Literacy in the Digital Space: A Study of Students at HKBP Nommensen University Pematangsiantar - Dian Tama Lidya Pardede; Wikky Pramudya Jasa; Rahel Nirmalasari Rajagukguk; Daulat Nathanael Banjarnahor (Yayasan Bayt Shufiya Nusantara, 2026)
This study aims to map digital media consumption patterns and evaluate national integration literacy among students at HKBP Nommensen University Pematangsiantar. Utilizing a quantitative approach with a composite index design, this study involved 32 student respondents from various academic disciplines. Descriptive analysis reveals that the internet has become the primary information infrastructure, with 84.4% of students relying on social media to consume national news (Accessibility Index score of 4.26). Affectively, technology functions as a reinforcement for national values, as evidenced by a exceptionally high Affective Integration Index score (4.38) and high appreciation for ethnic, religious, racial, and intergroup (SARA) diversity (93.8%). However, this study identifies an analytical gap in the Critical Capacity Index (3.92), indicating symptoms of cognitive overconfidence; students feel highly confident in their ability to verify hoaxes, whereas their actual literacy skills remain at a pragmatic-academic stage. This study concludes that higher education institutions must institutionalize critical digital literacy frameworks into curriculum policies to prevent disinformation and cultivate social harmony in the cybersphere.